The Analisis Kualitas Jasa Pelayanan Dengan Metode Service Quality (SERVQUAL) dan Quality Function Deployment (QFD) Di Bengkel Motor Radja Racing Bekasi - Alloysius Vendhi Prasmoro; Indira Sabila Syifa; Sonny Nugroho Aji (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
This research was conducted to analyze the quality of services provided by a Motor Radja Racing during this time to all customers. This paper aims to obtain an effective method to improve the quality of services previously existing in the repair Radja Racing Motor Workshop. The method of analysis done in this study using the Service Quality (SERVQUAL) and the method of Quality Function Deployment (QFD) that modeling in the form of House of Quality (HoQ). The results of this study indicate that the two methods is quite effectively used in analyzing the service quality that are in a Radja Racing Motor Workshop. In addition, the results of these two methods can be seen that the variables of service should be willing to do the repairs and improved is the variable reliability and to attribute is the number of mechanical comparable with the vehicles in service. On the other hand, through the method of servqual, QFD is used in enhancing and improving the quality of services that already exist coupled perform the evaluation of the state of the workshop of the motor. Keywords: Service Quality, Quality Function Deployment (QFD), House of Quality, Customer Satisfaction